Antiarrhythmic medication is superior to catheter ablation in suppressing supraventricular ectopic complexes in patients with atrial fibrillation. (1st October 2017) - Alhede, Christina; Lauridsen, Trine K.; Johannessen, Arne; Dixen, Ulrik; Jensen, Jan S.; Raatikainen, Pekka; Hindricks, Gerhard; Walfridsson, Haakan; Kongstad, Ole; Pehrson, Steen; Englund, Anders; Hartikainen, Juha; et al.
Abstract: Background: Supraventricular ectopic complexes (SVEC) originating in the pulmonary veins are known triggers of atrial fibrillation (AF) which led to the development of pulmonary vein isolation for AF. However, the long-term prevalence of SVEC after catheter ablation (CA) as compared to antiarrhythmic medication (AAD) is unknown. Our aims were to compare the prevalence of SVEC after AAD and CA and to estimate the association between baseline SVEC burden and AF burden during 24 months of follow-up. Methods: Patients with paroxysmal AF ( N = 260) enrolled in the MANTRA PAF trial were treated with AAD ( N = 132) or CA ( N = 128). At baseline and 3, 6, 12, 18 and 24 months follow-up patients underwent 7-day Holter monitoring to assess SVEC and AF burden. We compared SVEC burden between treatments with Wilcoxon sum rank test. Results: Patients treated with AAD had significantly lower daily SVEC burden during follow-up as compared to CA (AAD: 19 [6–58] versus CA: 39 [14–125], p = 0.003). SVEC burden increased post-procedurally followed by a decrease after CA whereas after AAD SVEC burden decreased and stabilized after 3 months of follow-up. Patients with low SVEC burden had low AF burden after both treatments albeit this was more pronounced after CA at 24 months of follow-up. Conclusion: AAD was superior to CA in suppressing SVEC burden after treatment of paroxysmal AF. After CA SVEC burden increased immediately post-procedural followed by a decrease whereas after AAD an early decrease was observed. Lower SVEC burden was highly associated with lower AF burden during follow-up especially after CA.